2005
DOI: 10.22358/jafs/67120/2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing feed with oregano and/or α-tocopheryl acetate on growth of broiler chickens and oxidative stability of meat

Abstract: An experiment was carried out to examine the effect of supplementing feed with oregano and/or α-tocopheryl acetate on growth performance of broiler chickens and the oxidative stability of breast and thigh meat. A total of 6300 one-day old Cobb-500 chickens were randomly allocated into 7 equal groups with three subgroups of 150 males and 150 females each. One of the groups was given a basal diet containing 30 mg α-tocopheryl acetate/kg feed (negative control group), whereas the other six groups were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 18 publications
5
41
0
Order By: Relevance
“…Similarly, it has been shown that essential oil compounds improved the performance of chickens at various levels of supplementation alone (Giannenas et al, 2003;Giannenas et al, 2005;Giannenas et al, 2013) or in combination with organic acids in chicken and turkeys (Giannenas et al, 2014a;2014b). Similar results were found by Windisch et al (2008) and Bozkurt et al (2012), who reported improved weight gain of broilers fed diets supplemented with essential oils, mainly OEO, which are rich in carvacrol and thymol.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, it has been shown that essential oil compounds improved the performance of chickens at various levels of supplementation alone (Giannenas et al, 2003;Giannenas et al, 2005;Giannenas et al, 2013) or in combination with organic acids in chicken and turkeys (Giannenas et al, 2014a;2014b). Similar results were found by Windisch et al (2008) and Bozkurt et al (2012), who reported improved weight gain of broilers fed diets supplemented with essential oils, mainly OEO, which are rich in carvacrol and thymol.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to organic acids, plant extracts offer a unique opportunity in this regard (Giannenas et al, 2005), as many plants produce secondary metabolites, such as saponins, tannins and polyphenols, which have antimicrobial properties. Essential oils (EO), plant extracts and certain herbs might be interesting alternative feed supplements to antibiotic growth promoters (Franz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many herbal plants such as rosemary, sage, thyme, oregano and tea or their extracts have attracted wide research interest due to their antioxidative, antibacterial and antifungal properties (Giannenas et al, 2003(Giannenas et al, , 2005 that are attributed to a great variety of phenolic compounds occurring in these plants. Moreover, thymol has intrinsic bioactivities on animal physiology and metabolism and, therefore, could have antioxidant activity in chicken meat when supplemented in the feed (Giannenas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the studies made to determine the antioxidant properties of oregano essential oil have been related to the LPO ratio [32,33] . In order to fully explain the mechanism the antioxidant effect of oregano essential oil must determine the rates of LPO and GSH with the SOD and CAT activities.…”
Section: Gümüş Erol İmi̇k Halicimentioning
confidence: 99%